Por uma pedagogia das fotonovelas : instruir e (in)formar leitoras do IERB durante os anos 60 e 70 do século XX - Albuquerque, Sônia Pinto Melo de (2015)
The pedagogy of women printed material, more specifically, the photo-novels, is the object of research of this Thesis, whose proposal is linked to the research line "History, Society and Educational Thought" of the Graduate Program in Education at the Federal University of Sergipe (UFS), in a special way, to the Group of Studies and Research in History of Education: Intellectuals on Education, Educational Institutions and School Practices and relates to theoretical and methodological assumptions of Cultural History, History of Women's Education, The History of the Printed and the History of Reading. It aims to search as leisure readings, in particular, of photo-novels, contributed to teach, from a specific pedagogy, to its readers, ways of being and behaving, enabling them to representations about the world in which they lived. Thus, in order to investigate about the pedagogy of female prints and photo-novels, I selected as reader community Pedagogy students from The Institute of Education "Rui Barbosa" (IERB) during the period of investigation of this object of study (decades of 60 and 70 in the 20th century), in order to know signs of behavior, values and experiences acquired in these readings, including such practices as relevant in the process of formation of this public reader. Therefore, to achieve this research, I discussed about reading practices, in particular, those relating to photo-novels, from the historical moment in which they are granted greater spread in the country, i.e. , between the decades of 60 and 70 in the 20th century. On the other hand, this period coincided with the industrial growth, expansion of consumption and greater accessibility to information. This way, to prove that the female prints and the photo-novels entered therein were carriers of a Pedagogy of values and cultures, I analyze the content of ten editions of the women's magazines of greater movement in the country, the Capricho magazine, six of them being from the 1960s and four, the 1970s of the 20th century, comprising, as parameter established by the Brazilian Institute of Geography and Statistics (IBGE), a generation (1960 to 1975), as well as my interviews with readers of these printed materials that are inserted in the community reader selected for this research. Finally, I support the thesis that leisure readings, in the specific case, magazines directed to women, as well as the photo-novels, reflected in the universe of their readers through a Pedagogy that provided them instruments of an over scholar education, revealing different female models, disseminated by accession and/or resistance, and that, in some way, served as inspiration for some young people about standards to be followed by physical, moral and socially.